Biochemical Profiles and Clinical Correlates of Hyperkalemia and Metabolic Acidosis in Acute Kidney Injury Patients: A Cross-Sectional Analysis: Electrolytic Imbalance in Acute Kidney Injury Patients - Talat, Muhammad Ali; Malik, Adan; Iqbal, Faisal; Asif, Huda; Khan, Anwar; Asif, Muhammad (Pakistan Journal of Health Sciences, 2025)
Acute Kidney Injury (AKI) is often complicated by biochemical disturbances, including hyperkalemia and metabolic acidosis. Objective: To examine the biochemical profiles and clinical consequences of hyperkalemia and metabolic acidosis in patients with AKI, with the goal of identifying correlations and prognostic markers to improve management strategies. Methods: The study analyzed 130 geriatric AKI patients with hyperkalemia and metabolic acidosis, assessing clinical outcomes through multivariable regression. Results: In 130 AKI patients with hyperkalemia and metabolic acidosis (mean age: 68.5 ± 10.2 years, 60% males), hypertension (45%) was the most common comorbidity. ICU admission was required in 25%, with an average hospital stay of 8.4 ± 4.5 days. Biochemical markers showed elevated serum potassium (6.2 ± 0.8 mEq/L), creatinine (3.5 ± 1.2 mg/dL), and reduced bicarbonate (18.5 ± 3.5 mEq/L). Serum creatinine (r = 0.80) and potassium (r = 0.67) correlated strongly with dialysis need, while lower blood pH (r = -0.50) was linked to ICU admission. Multivariable analysis identified serum creatinine (OR = 3.00, p < 0.001) as the strongest predictor of severe hyperkalemia and acidosis, with hypertension (OR = 2.15, p = 0.015) and advancing age (OR = 1.05, p = 0.003) also increasing risk. Conclusions: Hyperkalemia, metabolic acidosis, and elevated serum creatinine in acute kidney injury patients are strongly linked to worse outcomes, highlighting the need for early intervention.